Faktor-Faktor Yang Mempengaruhi I Distress Dengan Return On Assets (ROA) Sebagai Variabel Intervening - Siti Nur Asyifa, Alma; Khoirunnisa, Asyifa; Sudaryo, Yoyo; Herlinawati, Erna; Suryaningprang, Andre (GEMA EKONOMI, 2023)
This study aims to examine Current Ratio, Debt to Equity Ratio, Total Assets Turn Over, Quick Ratio, Return On Equity, Net Profit Margin to Financial Distress with Return On Assets as an intervening variable in companies affected by the Coronavirus Disease (COVID-19) pandemic. in Indonesia. The research sample was selected using a purposive sampling technique and resulted in one company with the 2011-2021 research period. This study uses a quantitative approach with secondary data through the documentation method. Data was obtained from the company's official website, the length of the Indonesian Stock Exchange (IDX), and other supporting periods. This study uses descriptive analysis and verification analysis using Microsoft Excel and SPSS 25. The results of this study indicate that Current Ratio (CR), Debt to Equity Ratio (DER), Total Assets Turn Over (TATO), Return on Assets (ROA) Return On Equity (ROE), and Net Profit Margin (NPM) have a significant effect on Financial Distress (FD), while Quick Ratio (QR) has no significant effect on Financial Distress (FD). Current Ratio (CR), Debt to Equity Ratio (DER), Total Assets Turn Over (TATO), Return On Equity (ROE), and Net Profit Margin (NPM) have a significant effect on Return On Assets (ROA), while the Quick Ratio ( QR) has no significant effect on Return On Assets (ROA).